2018
DOI: 10.1038/s41541-018-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the endoplasmic reticulum stress sensor IRE1α by the vaccine adjuvant AS03 contributes to its immunostimulatory properties

Abstract: The oil-in-water emulsion Adjuvant System 03 (AS03) is one of the few adjuvants used in licensed vaccines. Previous work indicates that AS03 induces a local and transient inflammatory response that contributes to its adjuvant effect. However, the molecular mechanisms involved in its immunostimulatory properties are ill-defined. Upon intramuscular injection in mice, AS03 elicited a rapid and transient downregulation of lipid metabolism-related genes in the draining lymph node. In vitro, these modifications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 55 publications
0
37
0
2
Order By: Relevance
“…Adjuvant-mediated innate immune activation via release of endogenous danger signals (danger associated molecular patterns, DAMPs) such as ATP, host DNA or uric acid has been described and likely plays a part in adjuvanticity for all particulate adjuvants 13 . Also the modulation of intracellular compartments and activation of the endoplasmatic reticulum stress sensor and subsequent metabolic changes have been observed for the emulsion adjuvant AS03 14 .…”
Section: Discussionmentioning
confidence: 90%
“…Adjuvant-mediated innate immune activation via release of endogenous danger signals (danger associated molecular patterns, DAMPs) such as ATP, host DNA or uric acid has been described and likely plays a part in adjuvanticity for all particulate adjuvants 13 . Also the modulation of intracellular compartments and activation of the endoplasmatic reticulum stress sensor and subsequent metabolic changes have been observed for the emulsion adjuvant AS03 14 .…”
Section: Discussionmentioning
confidence: 90%
“…Such adjuvant systems are known to augment antigen-specific T cell and antibody responses [57]. In a murine study, the ER stress-related pathway was found to potentially contribute to the adjuvanticity of AS03 in vivo [58]. Furthermore, the expression of the ER stress sensor kinase IRE1α by myeloid cells was involved in adjuvant activity of AS03.…”
Section: Induction Of Humoral Immunitymentioning
confidence: 99%
“…The ER stress-related pathway was required for AS03mediated induction of IL-6, robust Tfh responses, and antigenspecific antibody affinity maturation. IL-6 plays a crucial role in differentiation of Tfh cells as well as in the expression of IL-21 by Tfh cells and in production of antibodies [58].…”
Section: Induction Of Humoral Immunitymentioning
confidence: 99%
“…The underlying immunostimulatory mechanisms of various adjuvants have been investigated to develop human vaccines. A squalene-based oil-in-water emulsion, AS03, can induce immunostimulation via activation of IRE1α, an ER stress sensor (32). Glucocorticoids can contribute to immunostimulation on macrophages, which may be correlated to ER stress via the glucocorticoid receptor (33).…”
Section: Discussionmentioning
confidence: 99%